Pemeriksaan Fungsi Kognitif dengan Menggunakan Digit Symbol Substitution Test pada Siswa Sekolah Menengah di Kota Tangerang - Farhan, Fanny Septiani; Hafidz, Aditya; Khotimah, Adilah Hana (Pakis Journal Institute, 2025)
Cognitive function is a complex neurophysiological ability of the human brain, including memory, language, attention, executive, and visuospatial abilities. Some of the main factors that affect cognitive function include brain maturity, social experience, sleep quality, mental health, lifestyle, and nutrition. The Digit Symbol Substitution Test (DSST) is one of the instruments used to measure cognitive function. This community service was carried out on 283 students of Madrasah Aliyah Negri in Tangerang City with the aim of assessing students' cognitive function scores. The results of the DSST examination can be a reference for students to improve or enhance their cognitive function or as an initial screening to assess cognitive function decline.